The 100 Most Cited Articles on Dental Anomalies: a bibliometric analysis - Maria Eduarda Ferreira De Souza; Glenda Vieira De Sousa; Eloísa Cesário; Patrícia Santos (Cumhuriyet University, 2022)
Introduction: Dental anomalies (DA) are changes in the number, shape, structure, size and pattern of eruption of teeth and their etiology is multifactorial, early diagnosis and proper treatment are essential for an occlusal, functional and aesthetic harmony. Objective: To identify the 100 most cited articles on dental anomalies. Methods: A search was performed in the Thompson Reuters Web of Science (WOS) database on May 31, 2021. The search strategy was performed using the keywords obtained from the Medical Subject Headings (MeSH) index. The following data were extracted and analyzed: number of citations, title, authors, year of publication, title of scientific journals, type of study and subject field. Results: The search strategy resulted in 69,014 articles and the most cited studies were concentrated between 1945-2012, mainly in orthodontic journals. Twenty-four percent of all papers were published in orthodontic journals. Number of citations ranged from 98 to 482, and The United States was the most prolific country. Number anomalies and structural changes were the most studied thematic fields, totaling 79 articles. Laboratory studies were the most cited type of studies. Conclusion: Number anomalies and structural changes were the most studied thematic fields. There was a predominance of laboratory studies and The United States was responsible for most of the papers included.